THE EFFECT OF PRESSURE, TEMPERATURE, OXYGEN FUGACITY AND COMPOSITION ON PARTITIONING OF NICKEL AND COBALT BETWEEN LIQUID FE-NI-S ALLOY AND LIQUID SILICATE: IMPLICATIONS FOR THE EARTH'S CORE FORMATION - Li J.; Agee C.B. (My University, 2001)
Experiments have been conducted with a multi-anvil apparatus on two natural chondrites in four different sample containers. Partition coefficients for Ni and Co between liquid Fe-Ni-S-alloy and liquid silicate (DNiLA/LS and DCoLA/LS) were determined over a pressure range between 2 and 25 GPa and a temperature range between 2100 and 2623 K.Multi-variable linear regression analysis was performed on the measured DNiLA/LS and DCoLA/LS, using a formula that is partially based on thermodynamics and partially empirical relationships. The results from the experiments with non-graphite capsules revealed that the effects of oxygen fugacity are roughly consistent with Ni and Co being divalent ions in liquid silicate. Within the experimental pressure and temperature ranges, both Ni and Co become less siderophile with increasing pressure and temperature. The effect of pressure is more pronounced for Ni while the effect of temperature is more pronounced for Co. Furthermore, both effects become smaller at higher pressures and higher temperatures. Nickel and Co are less soluble in liquid silicate with higher degree of polymerization. The presence of S in liquid Fe-alloy enhances the siderophile behavior of Ni and Co. However, for a given relative proportion of Fe, Ni and Co in the Fe-alloy, DNiLA/LS and DCoLA/LS are larger for the Fe-alloy with a smaller S content.Applying the observed effects of pressure, temperature, oxygen fugacity and composition on DNiLA/LS and DCoLA/LS, we found that the observed partitioning of Ni and Co between core and mantle (DNic°re/mantle and DCoc°re/mantle) can be matched at high pressures and high temperatures. The pressure-temperature range corresponds to that in the current midmantle (about 1200-1450 km in depth). Therefore, the observed high abundances and near-chondritic ratio of Ni and Co in the Earth's upper mantle can be explained by chemical equilibrium between liquid Fe-Ni-S-alloy and liquid silicate in a deep magma ocean.